Principles for the Development of a Chemical Methodological System - Kholmurodova Laziza Erkinovna (Genius Journals, 2023)
The analysis shows that there are many important principles that need to be taken into account in the development of a methodological system for the training of a future chemistry teacher, and these principles are discussed in the article
Keywords: Chemistry; methodology; system; development